(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This research aims to investigate the microbial diversity of Budu prepared from fresh and frozen fish from the Pariaman and Pasaman districts in West Sumatra Province, Indonesia, as well as provide basic information about Budu quality. Materials and methods: To obtain the bacterial microbial composition, deoxyribonucleic acid extraction was carried out using amplicon-sequencing of the 16S-rRNA gene in the V3–V4 region from two types of Budu and carried out in duplicate. Results: Budu prepared with fresh (Pariaman) or frozen (Pasaman) fish was dominated by Firmicutes (78.455%–92.37%) and Proteobacteria (6.477%–7.23%) phyla. The total microbial species in Budu from Pariaman were higher (227 species) than in Pasaman (153 species). The bacterial species found are Lentibacillus kimchi (1.878%–2.21%), Staphylococcus cohnii (0.597%– 0.70%), Peptostreptococcus russeli (0.00%–0.002%), Clostridium disporicum (0.073%–0.09%), Clostridium novyi (0.00%–0.01%), Nioella sediminis (0.00%–0.001%), and Shewanella baltica (0.00%–0.003%). Lentibacillus kimchi, S. cohnii, and C. disporicum are found in both Budu. Nioella sediminis and S. baltica are found in Budu Pariaman. Peptostreptococcus russeli and C. novyi were found in Budu Pasaman. Conclusion: Metagenomic analysis of Budu from different fish, Pariaman (fresh fish) and Pasaman (frozen fish) showed that the biodiversity of bacteria was barely different. Both Budu found lactic acid bacteria from the Enterococcaceae family, genus Vagococcus, and pathogenic bacteria, such as S. cohnii, P. russeli, C. disporicum, and S. baltica. The discovery of various species of pathogenic bacteria indicates that development is still needed in the Budu production process to improve Budu quality. J. Adv. Vet. Anim. Res., 10(4): 801–808, December 2023 http://doi.org/10.5455/javar.2023.j736